Sanitary engineering a practical treatise on the collection, removal and final disposal of sewage and house refuse and the design & construction of works of drainage and sewerage with numerous hydraulic tables, formulae ... - Moore, E. C. S. (B.T. Batsford, 1901)
Chapters cover such topics as the flow of liquid in pipes and open channels; cesspool drainage systems; estimate of sewage and rainfall combined; and many useful formulae.
Keywords: Sanitary engineering.; elektronické knihy; electronic books